KV7 channel activation inhibits human and murine myometrium contractility and delays delivery in a mouse model of preterm birth - Yosef T. Mansour; Hiten D. Mistry; Evonne C. Chin-Smith; Mariola K. Zaleska; Deanna C. Sekulich; Jennifer L. Herington; Jeff Reese; Rima Patel; Philip I. Aaronson; Donna M. Slater; Sarah K. England; Iain A. Greenwood; et al. (Communications Medicine, 2026)
Abstract Background Spontaneous preterm birth, defined as delivery before 37 weeks of gestation, remains a global cause of neonatal illness and death, yet treatments for preterm labor remain limited. We hypothesized that K V 7 channels in the uterus (myometrium), could be a therapeutic target for preventing or treating preterm labor. The aim was to characterize K V 7 channel subtypes in human myometrium present after labor onset, and to use a preterm birth mouse model to provide proof-of-principal evidence that activating these channels in vivo can delay preterm delivery. Methods This experimental study integrated studies of human myometrial tissue (term and preterm pregnancies, n = 159 across experiments), with a RU486-induced preterm birth mouse model (C57BL/6 J, n = 6-9 per experimental group), and ex vivo fetal ductus arteriosus preparations (CD-1 mice, n = 10 per group). Molecular and protein profiling, isometric tension recordings, and functional pharmacology were used to characterize K V 7 mediated regulation of human and mouse uterine contractility. In vivo dosing studies in mice assessed the effects of K V 7 activators (retigabine and ML213) on delivery timing ( n = 6-9). Results We show that K V 7 channels and ancillary units (KCNE1-5), are expressed in pregnant human myometrium, prior to and after the onset of labor. KCNQ4 and KCNE4 transcripts are also present in myometrium taken at preterm gestations ( ± labor). K V 7.2-5 activators markedly reduce spontaneous contractions in human and mouse myometrium in vitro and significantly delay preterm birth in vivo with limited impact on fetal ductus arteriosus function. Conclusions These findings support K V 7 activation as a promising approach to suppress uterine contractility and hence delay preterm birth, highlighting a potential new direction for either drug repurposing or therapeutic development.